Best Practices of Social Media in Academic Libraries: A Case Study of Selected Engineering College Libraries of Odisha - Sahu, Mahendra K. (DESIDOC Journal of Library & Information Technology, 2016)
The way the social media tools are strengthened with the impact of proliferating portable computing, wireless technologies, and other web application, have re-designed how information is generated, communicated and consumed in an academic library. The present paper examines the extent to which social media tools impact the most on libraries of engineering colleges of Odisha. An online survey has been conducted by sending online questionnaires librarians affiliated to BPUT Odisha.